2017
DOI: 10.18632/oncotarget.17359
|View full text |Cite
|
Sign up to set email alerts
|

Lipid catabolism inhibition sensitizes prostate cancer cells to antiandrogen blockade

Abstract: Prostate cancer (PCa) is the most common malignancy among Western men and the second leading-cause of cancer related deaths. For men who develop metastatic castration resistant PCa (mCRPC), survival is limited, making the identification of novel therapies for mCRPC critical. We have found that deficient lipid oxidation via carnitine palmitoyltransferase (CPT1) results in decreased growth and invasion, underscoring the role of lipid oxidation to fuel PCa growth. Using immunohistochemistry we have found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 51 publications
3
74
0
Order By: Relevance
“…ATP and NADH are known to provide a survival advantage to cancer cells 19 and thus might contribute to cisplatin resistance as well. In concordance with our study, FAO inhibition has been shown to cause chemosensitization by limiting ATP supply in prostate cancer 43 and leukemia cells 44 .…”
Section: Discussionsupporting
confidence: 92%
“…ATP and NADH are known to provide a survival advantage to cancer cells 19 and thus might contribute to cisplatin resistance as well. In concordance with our study, FAO inhibition has been shown to cause chemosensitization by limiting ATP supply in prostate cancer 43 and leukemia cells 44 .…”
Section: Discussionsupporting
confidence: 92%
“…1 ), whereas CPT2 is located in the inner mitochondrial membrane. CPT1A is overexpressed in prostate cancer and is associated with a high tumor grade [ 193 , 194 ]. High expression levels of CPT1A predict unfavorable clinical outcomes in AML [ 195 ] and ovarian cancer [ 196 ].…”
Section: Key Modulators Of Lipid Metabolism In Cscsmentioning
confidence: 99%
“…High expression levels of CPT1A predict unfavorable clinical outcomes in AML [ 195 ] and ovarian cancer [ 196 ]. Genetic or pharmacological inhibition of CPT1A exerts anti-tumor activity in prostate cancer [ 193 ], melanoma [ 197 ], breast [ 198 ], and ovarian cancer [ 196 ]. CPT1A is required for stem cell maintenance in neural stem/progenitor cells (NSPCs) [ 138 ].…”
Section: Key Modulators Of Lipid Metabolism In Cscsmentioning
confidence: 99%
“…We found CPT1 family members to be down-regulated by BAY-3827, supporting a similar pathway to be implicated in prostate cancer growth. Recent knock-down and overexpression studies underline the role of CPT1 and β-oxidation in prostate cancer growth and treatment resistance [45,46]. Indeed, the determination of lipid content in treated cells showed that whereas androgen had little direct impact on lipid droplet formation, the treatment with BAY-3827 led to a signi cant accumulation of intracellular lipids, most likely due to the observed down-regulation of the CPT1 family members.…”
Section: Discussionmentioning
confidence: 99%